EFFECT OF GUIDED INQUIRY ON STUDENT’S ACHIEVEMENT IN BIOLOGY (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This paper investigates the effect of guided inquiry and lecture methods on  students’ academic achievement in biology in senior secondary schools in  Rivers State.    Two  research questions and two null hypotheses tested at 0.05 level of significance guided  the study.  The sample of the study was 407 SSII biology students drawn by Purposive  sampling  technique  in  which  four  schools  were  selected  from eight senior secondary schools in the area of study.  The sample consisted of 223 boys and  184 girls.   The classes used  for the study were selected by simple  random  sampling  using  the   ballot  system.  Mean,  grand   mean, standard deviation and t-test  statistic were used to analyze data from the result of Biology Achievement  Test used  for data collection.   The  result shows that mean pretest scores of the experimental and control groups used for  the  study  are  insignificant.   The  mean  posttest  scores  show  a  wide difference.   There is  a significant difference between the achievements of students taught with guided inquiry and those taught with lecture method in favour of guided inquiry.  Guided inquiry proved more effective than lecture method   in    enhancing    students’    academic    achievement   in   biology. Recommendations are made from the findings of the study.